2006
DOI: 10.4142/jvs.2006.7.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of doxycycline in ostriches (Struthio camelus) at two different dose rates

Abstract: A bioavailability and pharmacokinetics study of doxycycline was carried out on 30 healthy ostriches after a single intravenous (IV), intramuscular (IM) and oral dose of 15 mg/kg body weight. The plasma doxycycline concentration was determined by HPLC/UV at 0 (pretreatment), 0.08, 0.25, 0.5 1, 2, 4, 6, 8, 12, 24 and 48 h after administration. The plasma concentration-time curves were examined using non-compartmental methods based on the statistical moment theory for only the higher dose. After IV administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
4
11
3
Order By: Relevance
“…Therefore, the present study could be further refined to determine the influence of age on the pharmacokinetics of doxycycline in ducks after different routes of administration. The Vss of doxycycline reported here was 0.590.89 ml/kg, consistent with that in 12-week-old turkeys (0.530.17 l/kg, Santos et al, 1997), higher than in chickens (0.110.01 l/kg, Anadon et al, 1994), but lower than in ostriches (0.860.16 l/kg, Abu-Basha et al, 2006), and in 3 d, 3-, and 6-week-old turkeys (1. 770.22, 2.140.24, and 0.650.35 l/kg, respectively, Santos et al, 1997).…”
Section: Pharmacokinetic Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, the present study could be further refined to determine the influence of age on the pharmacokinetics of doxycycline in ducks after different routes of administration. The Vss of doxycycline reported here was 0.590.89 ml/kg, consistent with that in 12-week-old turkeys (0.530.17 l/kg, Santos et al, 1997), higher than in chickens (0.110.01 l/kg, Anadon et al, 1994), but lower than in ostriches (0.860.16 l/kg, Abu-Basha et al, 2006), and in 3 d, 3-, and 6-week-old turkeys (1. 770.22, 2.140.24, and 0.650.35 l/kg, respectively, Santos et al, 1997).…”
Section: Pharmacokinetic Analysissupporting
confidence: 92%
“…In the present study, the volume of distribution (Vz) of doxycycline in ducks after IV administration was 1.760.33 l/kg, in accordance with that in ostriches (1.67±0.52 l/kg, Abu-Basha et al, 2006), but higher than that reported in chickens (0.280.02 l/kg, Anadon et al, 1994). Santos et al (1997) reported that the Vz of doxycycline in 3 d, 3-, 6-and 12-week-old turkeys were 2.83±0.19, 4.10±0.40, 1.26±0.51 and 0.85±0.02 l/kg, respectively, which indicated that the V z of doxycycline in turkeys decreased with increasing age.…”
Section: Pharmacokinetic Analysissupporting
confidence: 86%
See 2 more Smart Citations
“…Bacteria [1]. It is a bacterioststic agent having a broad spectrum activity against Gram-positive and Gram-negative anaerobic and aerobic bacteria, Mycoplasmas, Chlamydiae, Rickettsiae, and some Protozoa [2]. Doxycycline was firstly invented and clinically developed by Pfizer Inc., New York in the early 1960s and marketed under the trade name Vibramycin [3] [4].…”
Section: Introductionmentioning
confidence: 99%